Desenvolvimento de hambúrguer de Piavuçu (Leporinus macrocephalus) adicionado de proteína texturizada de soja - Cardoso, Daiane Alves (2015)
For the development of a new product, we seek to meet the needs of industry, market and consumer in quality parameters, convenience and nutritional value that refers to good health. In order to develop the hamburger product piavuçu fillet for the fish value addition, it was established the physical-chemical, microbiological and sensory for 120 days of storage to verify the product's life during this period. Hamburger three formulations were prepared, added texturized soybean protein (TSP), namely T1 = 0%; T2: 2% and T3: 4%. For the physico-chemical analysis was performed chemical composition, and protein content, moisture, lipids and ash, microbiological analyzes of Salmonella, Staphylococcus aureus, coliforms termolerantes, mesophilic and psicotróficos, and sensory analysis product acceptance and judgmental profile in which it was carried out with 82 panelists. The results of microbiological analyzes of burgers remained within the required by Brazilian law, throughout storage time. The results of the analyzes chemical composition was no difference between the samples (p> 0.05) between the ash and moisture, as for lipids and protein did not differ between treatments. For the sensory analysis acceptance test was no significant difference (p ≤ 0.05), between treatments for the attributes of juiciness and overall appearance. There was a higher purchase intent for treating 2 with 47%. The process of drawing up burgers to filet piavuçu base was successfully obtained proving to be possible to use low commercial value fish in product development, thus adding value to the fish.